2010
DOI: 10.1089/jwh.2008.1206
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Transdermal Nonpatch Estrogen Therapy for the Management of Menopausal Symptoms

Abstract: During the transition into menopause, women may experience a wide range of symptoms that negatively impact quality of life. The vasomotor symptoms (VMS) of hot flushes and night sweats are common and vary widely in frequency and severity. The treatment of menopause-associated VMS is a frequently encountered clinical challenge, with the goal of tailoring treatment for each individual woman's needs. Estrogen therapy is the most effective treatment for menopausal VMS. Current guidelines suggest that estrogen ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…It is also worth mentioning that transdermal E2 has been commonly prescribed for postmenopausal women in Europe for decades, but oral estrogens remain the mainstay of treatment in the U.S. [27]. Transdermal E2 should provide all the benefits of hormone therapy without elevating cardiovascular or neurological disease risk, in accordance with supporting laboratory and clinical E2 cardioprotection and neuroprotection studies.…”
Section: Evidence For a Critical Period Of E2 Replacementmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also worth mentioning that transdermal E2 has been commonly prescribed for postmenopausal women in Europe for decades, but oral estrogens remain the mainstay of treatment in the U.S. [27]. Transdermal E2 should provide all the benefits of hormone therapy without elevating cardiovascular or neurological disease risk, in accordance with supporting laboratory and clinical E2 cardioprotection and neuroprotection studies.…”
Section: Evidence For a Critical Period Of E2 Replacementmentioning
confidence: 98%
“…Considering this effect, it is no surprise that oral CEEs are associated with increased risks for VTE and ischemic stroke. However, since transdermal E2 bypasses the gut and liver entirely, transdermal HT seems to be a logical, intuitive, and safer option for menopausal women [27, 92, 167, 175]. In fact, as mentioned earlier, the ESTHER study observed a 4-fold increased risk of VTE in oral HT users versus nonusers but no increased risk of VTE in transdermal HT users [25].…”
Section: Evidence For a Critical Period Of E2 Replacementmentioning
confidence: 99%
“…9 By July 2003, 12 months after the initial WHI publication, HT use had decreased between 32% and 38%, 10,17 and by 18 months post-WHI, HT use was nearly 45% below mid-2002 levels. 18 Evolving data affecting the benefit-risk ratio of HT, 19 as well as the continued refinement of menopause treatment guidelines 20,21 and the addition of new therapies to the armamentarium of HT options, 22 may have further altered recent HT utilization. Although data have begun to emerge on physicians' prescribing patterns and opinions of HT post-WHI, no recent long-term evaluation of HT prescription trends in the United States has been published.…”
mentioning
confidence: 99%
“…After closure of the estro-progestogen arm of the WHI (2002), some researchers admitted that not all estrogens and progestogens are alike, and alternative drugs, doses, and delivery systems may exhibit better safety profiles than CEE/MPA (with co-multiple and complex studies of the WHI), with no loss of efficacy [5,6]. The next subchapters will present the transdermal/percutaneous route for estrogens, the vaginal route for micronized progesterone, and the intrauterine systems with levonorgestrel/progesterone for recommendation in menopause transition-early and late perimenopause and early postmenopause from the road of menopause [2].…”
Section: Non-oral Versus Oral Route For Hormone Therapy Administratiomentioning
confidence: 99%